The effect of nanosecond ultrawideband electromagnetic radiation on xenogeneic erythrocytes - Gordienko, E.A.; Gordienko, O.I.; Rozanov, L.F.; Rozanova, E.D.; Gaponenko, N.I.; Gorozhanin, D.V.; Yegorov, O.M.; Kravchenko, V.A.; Lonin, Yu.F.; Onishchenko, N.I. (Вопросы атомной науки и техники, 2001)
Experiments were the intention to investigate the effect of short-pulse ultrawideband electromagnetic radiation on biological objects. An insulated rod antenna excited by a high-current electron beam (E ~ 0.5 to 1.0 MeV, I ~ 4 to 10 kA, τ ≈ 15 ns) served as a radiation source. The objects to be irradiated, i.e., erythrocytes of both donors and diabetics, were put in the regions with field intensity varying from 100 to 1000 V/cm. The effect of radiation on the lifetime and shape of erythrocytes on the permeability of erythrocyte membranes for the penetrating nonelectrolyte (1 M glycerin) and the state of intracorpuscular hemoglobin was investigated by the methods of small-angle light scattering, UV spectrometry and phase-contrast microscopy.